ANÁLISE E CAUSAS DAS MANIFESTAÇÕES PATOLÓGICAS ENCONTRADAS EM UM CONDOMÍNIO RESIDENCIAL NA CIDADE DE GUARAÍ NO ESTADO DO TOCANTINS (REMUNOM, 2024)
The practice of building homes as shelter dates back to ancient human history. In contemporary times, advances in construction aspects have resulted in the evolution of materials used in civil construction, bringing substantial benefits. However, challenges such as the shortage of qualified labor, inefficient execution techniques and the use of materials of questionable quality hamper construction. This, in turn, leads to the emergence of pathological manifestations, causing discomfort and safety risks. This article consisted of a case study that reaffirms its points through bibliographical research. The article's construction period was between May 2023 and March 2024. The field visit was carried out to survey the manifestations found, the investigation of their causes was carried out through anamnesis and was based on a bibliographic review. The results obtained pointed out the main pathological manifestations found in situ. The main manifestations found during the visit were: Infiltration, cracking, fissures, floor detachment and mold.